Demonstration of the cryoprotective properties of the fucose-containing polysaccharide FucoPol. (1st October 2020) - Guerreiro, Bruno M.; Freitas, Filomena; Lima, João C.; Silva, Jorge C.; Dionísio, Madalena; Reis, Maria A.M.
Graphical abstract: Highlights: FucoPol increased post-thaw cell viability of multiple cell lines. Good cryoprotective effect was achieved at a low concentration of 2.5 mg/mL. FucoPol showed no cytotoxicity and cell morphology was preserved. FucoPol showed calorimetric behavioural similarities to an antifreeze protein. FucoPol induced premature crystal growth, thus promoting reduced crystal sizes. Abstract: We report the cryoprotective potential of FucoPol, a fucose-containing bacterial exopolysaccharide produced by Enterobacter A47. In vitro cryopreservation assays of Vero, Saos-2, HFFF2 and C2C12 cell lines exposed to a validated non-cytotoxic 2.5 mg/mL FucoPol concentration demonstrated a consistent post-thaw metabolic viability increase. Calorimetric analysis showed a non-colligative, FucoPol concentration-dependent increase of the freezing point ( T f ), with minimal change in melting point ( T m ). Freezing point variation was corroborated by Polarized Optical Microscopy studies, also showing a reduction of ice crystal dimensions. Its proven shear-thinning behaviour and polyanionicity favour interactivity between the polysaccharide and the water-ice interface, resulting in ice growth inhibition. These findings demonstrate FucoPol's high promise as a bio-based, biodegradable approach to be implemented into cryopreservation formulations.